Efeito da melatonina no sêmen criopreservado de curimba (Prochilodus lineatus) - Assis, Isadora de Lima (2017)
Considering that oxidative damages observed during the semen freezing process are one of the main causes of the decrease of its viability, and that the melatonin supplementation is capable of increasing the sperm tolerance after thawing, the objective of this work was to evaluate the effects of the addition of different doses of melatonin on the parameters like motility, morphology and fertilization capacity of the cryopreserved semen of Prochilodus lineatus. After males’ hormonal treatment with carp pituitary extract and seminal collection, four groups were set with the homogenized semen of two animals and diluted in solutions containing: Positive Control (C+): BTS (5%) + DMSO (8%), and the treatments T1, T2 and T3: BTS (5%) + DMSO (8%) plus concentrations of 1, 2 and 3mM of melatonin, respectively. The diluted semen was placed in straws of 0.5 ml and frozen in a cylinder of vapor nitrogen (dry shipper), where the temperature decrease occurred from 35.6 degrees per minute until the temperature of -170°C. After the frozen process, the straws were stored in a nitrogen cylinder at -196 o C until thawing. Five months after freezing, the straws were thawed in a water bath at 40°C for 12 seconds in order to conduct the analysis of sperm motility and morphology. One year after freezing the fertilization rate evaluation was made. The parameters of total and progressive motility rate, curvilinear velocity (VCL), linear velocity (VSL) and mean velocity (VAP) of the semen after thawing were determined using the computerized semen analysis system (SCA). The data were submitted to analysis of variance, and the means were compared by the Tukey test (P <0.05). There were no differences (P >0.05) between the progressive motility rates and the velocities (VCL, VSL and VAP) of the cryopreserved semen in the different treatments. The total motility rate was higher (P <0.05) in the groups containing 1 and 2mM of melatonin when compared to T3, but they did not differ from C+. For morphology analysis, the percentage of sperm abnormalities increased with the cryopreservation process (P <0.05). However, all treatments had similar values after thawing of total anomalies and did not differ in fertilization capacity (P> 0.05). In conclusion, with these results it is possible to infer that the addition of melatonin to the cryoprotetant solution of curimba semen was not able to promote greater viability to the cryopreserved semen.